(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The purpose of the research was to develop a profile for the psycho-pedagogical professional working in non-governmental organizations whose population has autism spectrum disorder. The study is located within the naturalistic paradigm, with a qualitative approach and the type of research is phenomenological. Six semi-structured interviews were conducted: three with mothers of people with ASD and three with professionals in psychopedagogy with experience in this population, linked to the TEA Foundation Costa Rica, Belen Foundation and the Association of People with Autism of Quepos (APAQ) during the year 2024. The results show that there is still a lack of knowledge about this disorder, which is detrimental to the schooling process of those with this condition. As a final product, a profile was elaborated, based on the categories of analysis of the research, which gathers the basic elements that every psychoeducationalist working with people with ASD should aspire to fulfill.